Magic efficiency of approximation of smooth functions by weighted means of two $N$-point Padé approximants - Gilewicz, J.; Jedynak, R. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We consider the approximation of smooth functions by two weighted $N$-point Pad´e approximants. We present numericalexamples and the inequalities between the Stietjes function and its $N$-point Padé approximant.Квартиры посуточно - онлайн-бронирование